Blood donors’ experiences and perceptions of donation at a Peruvian public hospital - Arias Quispe, Sergio (2018)
Objective: To know the experiences and perceptions of blood donors at a public hospital. Materials and methods: A qualitative study with phenomenological orientation was performed at a public hospital in Lima. Semi-structured in-depth interviews and field notes based on participants' observations were conducted. Results: A total of 12 donors who reported not having much information about donation and blood banks were interviewed. However, after their donation experience, they identified positive aspects such as a high-quality, fast and thorough care. Participants appreciated the personnel’s cordial treatment when providing information, the short waiting time, and the personnel’s company during the process of blood extraction. The negative aspects were the lack of dissemination and publicity of voluntary blood donation. In spite of this, most interviewees expressed their intention to return due to the high-quality service they received. In summary, participants’ perception of blood donation was favorable because they received high-quality care, with timely information in the appropriate time. Conclusions: Interviewees had limited information about the possibility of making voluntary blood donations at the hospital. After their experience, participants perceived that donating blood was favorable and indicated their intention to participate in future donations.